Improvement of Peri-Implant Repair in Estrogen-Deficient Rats Fed a Cafeteria Diet and Treated with Risedronate Sodium - Silva, Ana Cláudia Ervolino da [UNESP]; Batista, Fábio Roberto de Souza [UNESP]; Hassumi, Jaqueline Suemi [UNESP]; Palin, Letícia Pitol [UNESP]; Monteiro, Naara Gabriela [UNESP]; Frigério, Paula Buzo [UNESP]; Okamoto, Roberta [UNESP] (MDPI, 2022)
(1) Background: Postmenopausal osteoporosis combined with an unhealthy lifestyle can lead to the development of metabolic syndrome, a common condition in individuals requiring oral rehabilitation. Bisphosphonates are used to increase bone mineral density. However, further studies are needed to evaluate the action of this drug on the bone repair process in the jaws. The aim of this study was to evaluate the peri-implant repair of rats with estrogen deficiency and metabolic syndrome treated with risedronate sodium. (2) Methods: Twenty-four female Wistar rats were divided into three groups: SHAM: sham surgery; OVX/SM: ovariectomy combined with a cafeteria diet; OVX/SM/RIS: ovariectomy associated with a cafeteria diet and treatment with sodium risedronate. After 30 days, the animals underwent extraction of the upper first molars. Thirty days after the extraction, an implant was installed in the same region. Sixty days after the implant was installed, the animals were euthanized for biomechanical analysis and confocal microscopic analysis. After confirming the normal distribution of the sample data, a one-way ANOVA test was performed, followed by Tukey’s post-test, with a 5% significance level. (3) Results: Significant bone preservation was observed in the risedronate-treated group. Higher removal torque values were obtained by the risedronate-treated group. (4) Conclusions: Better biomechanical performance of the implants installed in the animals treated with risedronate sodium was observed.
Keywords: metabolic syndrome; osteoporosis; ovariectomy; risedronic acid